LOANWORDS FOUND IN BALI AND BEYOND MAGAZINES - Putu Gede Wiyana Nararya Nginte; Kadek Adi Indra Brata (Universitas Warmadewa, 2018)
The aim of this study is to know the types and the reason of using loanword found in Bali and Beyond Magazine. Another specific reason is to find out how many the loanword is used in these magazines. The data were collected by using observation method then they were analyzed by identifying the loanwords found in the magazines, then categorizing whether it is loanwords based on the level, loanwords based on the language involved and loanwords based on the frequency. Based on the analysis above, there are three types of loanwords: (1) loanwords based on the level that can be divided into two, they are: necessary loanword and unnecessary loanword, (2) loanword based on the language involved that can be divided into two, they are: loanword as culture and loanword as intimate and (3) loanword based on the frequency that can be divided into two, they are: loanword as speech borrowing and loanword as language borrowing.